2022
DOI: 10.1038/s41538-022-00169-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stronger gut microbiome modulatory effects by postbiotics than probiotics in a mouse colitis model

Abstract: Probiotics are increasingly used as adjunctive therapy to manage gastrointestinal diseases, such as ulcerative colitis. However, probiotic use has posed some safety concerns. Thus, postbiotics are proposed as alternatives to probiotics in clinical applications. However, no study has directly compared the clinical benefits of probiotics and postbiotics. This study compared the beneficial effect of postbiotics and probiotics derived from the strain, Bifidobacterium adolescentis B8598, in a dextran sulfate sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Consistent with the results in this study, Zhang et al found that both probiotics and postbiotics can alleviate DSSinduced intestinal injury. 56 Tight junction (TJ) is the most important structure to maintain the integrity of the epithelial layer; it consists of four types of transmembrane proteins: clau-…”
Section: Papermentioning
confidence: 99%
“…Consistent with the results in this study, Zhang et al found that both probiotics and postbiotics can alleviate DSSinduced intestinal injury. 56 Tight junction (TJ) is the most important structure to maintain the integrity of the epithelial layer; it consists of four types of transmembrane proteins: clau-…”
Section: Papermentioning
confidence: 99%
“…More recently, the application of the so-called postbiotics has been addressed [ 187 ]. Postbiotics are classified as non-viable bacterial products or functional bioactive compounds resulting from the fermentation of probiotic microorganisms aiming to confer health on the host [ 188 ]. For instance, inosine, butyrate, or propionate could modulate the efficacy of immune checkpoint inhibitors [ 170 , 189 ].…”
Section: The Microbiota As Target Therapymentioning
confidence: 99%
“…Postbiotics in the form of heat-killed bacteria or their metabolites have been shown to be able to improve health in some preclinical and clinical studies. For example, our previous study compared the therapeutic effects of administering live or dead Bifidobacterium adolescentis B8589 in dextran sulfate sodium (DSS)-induced colitis mice, and surprisingly found that heat-killed Bifidobacterium adolescentis B8589 had better anti-inflammatory and symptom-mitigating effects compared to live bacteria . Because postbiotics are nonviable, there is no requirement for gut colonization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our previous study compared the therapeutic effects of administering live or dead Bifidobacterium adolescentis B8589 in dextran sulfate sodium (DSS)-induced colitis mice, and surprisingly found that heat-killed Bif idobacterium adolescentis B8589 had better anti-inflammatory and symp- tom-mitigating effects compared to live bacteria. 14 Because postbiotics are nonviable, there is no requirement for gut colonization. Instead, their mechanisms of action rely more on enhancing the growth of native probiotics in the host colon and promoting downstream pathways that are beneficial to the host to improve colonic homeostasis.…”
Section: Introductionmentioning
confidence: 99%